Teachers and loneliness: The children's perspective - Galanaki, Evangelia (School Psychology International, 2004)
The aim of this study was to investigate children‘s perceptions (i.e. expectations) of the interventions that teachers should implement to deal with their loneliness. The role of significant others in children‘s attempts to cope with loneliness and the children‘s perceptions of that role have been neglected by researchers. A random sample of 180 second, fourth and sixth graders from Athens, the capital of Greece, were individually interviewed. Qualitative analysis using the ‘concept-indicator model‘ (Strauss, 1987) showed that school-age children have an adequate understanding of the loneliness alleviation strategies that teachers can and should use. The strategies may be distinguished into the two already known broad categories of coping, that is problem-focused or active coping strategies (i.e. manifestation of interest and care, intervention in the peer group, encouragement to approach peers and make friends, consultation for personal improvement, informing parents), and emotion-focused or avoidance coping strategies (i.e., emotion regulation, encouragement to engage in activities and inability to cope). Results are discussed in terms of their implications for the role of the teacher in alleviating loneliness, for school-based interventions with this purpose, as well as for their contribution in the existing knowledge about coping with loneliness strategies.